Imunitas Negara Asing Di Depan Pengadilan Nasional Dalam Kasus Pelanggaran HAM Yang Berat Konsekuensi Hukum Jus Cogens Terhadap Imunitas Negara - Author: Sefriani (Fakultas Hukum Universitas Islam Indonesia, 2010)
Gross violation on human right has been occurred at many countries. Almost all of the perpetrators are state .In international law foreign state has immunity before national court. Developing of international law showed that in one side gross violation on human right is prohibited and has a status as jus cogens, peremptory nom under international law. However foreign state immunity before national court is fundamental right. International law doesn’t strictly and clearly governed legal consequences jus cogens norm over gross violation on human right. Some of national court remaining recognized state immunity to foreign state with some legal reason. However others national court denied that immunity.Key words : law’s consequences, state’s immunity, the International law